Mobile Postoperative Symptom Intervention Tool and Biometric Monitoring After Radical Cystectomy: Pilot Study Evaluating Feasibility, Usability, and Potential Utility. Issue 2 (9th November 2022) - Huelster, Heather L.; Zemp, Logan; Turner, Kea; Gonzalez, Brian D.; Jim, Heather; Gore, L. Robert; Gilbert, Scott M.
Abstract : Purpose: Mobile health technology and integration of patient-reported outcome measures into clinical interventions have the potential to transform patient care. Though patient-reported outcome measure management has been shown to improve outcomes in ambulatory care settings, few studies have examined remote patient-reported outcome measure assessment after major cancer surgery. Materials and Methods: A multiphased feasibility and usability study was designed. A mobile app-based postoperative symptom intervention tool was developed and evaluated by a focus group of bladder cancer patients and caregivers. Patients were prospectively accrued prior to cystectomy and asked to complete the daily mobile postoperative symptom intervention tool and wear biometric monitoring devices for 30 days post discharge. Retention, postoperative symptom intervention tool completion, and usability were assessed. Exploratory analysis of daily symptoms and patient-generated health information correlated signals with postsurgical complications and hospital readmission. Results: Fifteen patients with a median age of 72 years completed 78% of daily surveys over the 30-day recovery period. Average time to complete the postoperative symptom intervention tool was 152 seconds. All patients agreed that the daily survey was easy to use, and most reported it would be a better way to communicate with the care team about symptoms than calling the clinic. Frequency and severity of patient-reported symptoms appeared to cluster prior to or at the time of complication or unplanned health care encounters on visual-analogue mapping. Conclusions: Using smartphone and wearable technology to capture patient-reported symptoms and biometric data is feasible and rated as highly usable by bladder cancer patients after cystectomy. Symptom scores may signal developing complications and help clinicians identify postsurgical patients who may benefit from intervention.